The Corn Model, Gluts and Surplus Value. - Glyn, A (Department of Economics (University of Oxford), 2004)
The controversy over Ricardo’s corn model has focussed on the interpretation of his early writings. Here Ricardo’s later use of a corn model example in his dispute with Malthus over gluts is discussed. Malthus’s own extensive use of a corn model in attempting to justify his use of a labour commanded measure of value is analysed; it is shown that he calculates what Marx was to describe as surplus vale from the physical conductions of production and the real wage.